2019
DOI: 10.1103/physrevd.99.103019
|View full text |Cite
|
Sign up to set email alerts
|

Probing DAMA/LIBRA data in the full parameter space of WIMP effective models of inelastic scattering

Abstract: We discuss the compatibility of the combined annual modulation effect measured by DAMA/LIBRA-phase1 and DAMA/LIBRA-phase2 with an explanation in terms of inelastic scattering events induced by the most general Galilean-invariant effective contact interaction of a Weakly Interacting Massive Particle (WIMP) dark matter particle of spin 0, 1/2 or 1. We take into account all the possible interferences among operators by studying the intersections among the ellipsoidal surfaces of constant signal of DAMA and other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 104 publications
2
40
0
Order By: Relevance
“…Recently analyses of the inelastic DM candidate with SD coupling have been reported in Refs. [64,65]. They show that also this scenario can be compatible with the DAMA result.…”
Section: Inelastic Dark Mattersupporting
confidence: 69%
“…Recently analyses of the inelastic DM candidate with SD coupling have been reported in Refs. [64,65]. They show that also this scenario can be compatible with the DAMA result.…”
Section: Inelastic Dark Mattersupporting
confidence: 69%
“…In Ref. [7] we also considered an extension of the present analysis to the case of the most general Galilean-invariant WIMP-nucleon effective contact interaction for a spin 0, 1/2 or 1 WIMP dark matter following the approach introduced in [8] and checked the compatibility of the DAMA effect in an inelastic scattering scenario. In particular in that analysis, we also included all possible interferences among operators and found that in comparison to the elastic case discussed in [8], inelastic scattering partially relieves but does not eliminate the existing tension between the DAMA effect and the constraints from other experiments, when a Maxwellian velocity distribution for WIMPs is considered.…”
Section: Discussionmentioning
confidence: 99%
“…Although inelastic dark matter scattering has been studied in-depth in the context of models to explain the DAMA excess [38,42,[56][57][58], it is in fact a generic feature of some classes of dark matter models. While we will not explore particular inelastic dark matter models for the purpose of this paper, we provide the following as an illustrative example.…”
Section: Introductionmentioning
confidence: 99%